KAJIAN PENGEMBANGAN POTENSI KAMPUNG ADAT PRAIYAWANG SEBAGAI KAWASAN WISATA BUDAYA DI DESA RINDI KABUPATEN SUMBA TIMUR NUSA TENGGARA TIMUR - Nau, Dominggus Pati Maramba; Setyabudi, Irawan; Hamzah, Amir (Fakultas Pertanian, 2019)
Praiyawang traditional village is a traditional village in Rindi Village, Rindi District, East Sumba Regency. The landscape characteristics of the Praiyawang village area consist of physical and biophysical characteristics. Physical characteristics include, elements forming the landscape and spatial layout of the area.The shape of the landscape forming of Praiyawang area is Uma batang (tower house), katuada (menhir), retaining maramba (tomb grave), menhir, sabana field. The spatial structure consists of macro, table and micro space. Macro spatial planning includes landscape spatial planning that supports all people's lives consisting of forest space, agriculture, settlements, and savannas. The meso room is part of the macro space which consists of the settlement environment of the indigenous village communities of Praiyawang. Meso space consists of residential building elements, namely Uma, Menhir, Reti, Penji, Katuanda and Vegetation. The distribution of community houses in the praiyawang traditional village has a circular pattern of settlements with lined up intersecting megalithic graves. Micro space includes the house and yard. The micro spatial of the Praiyawang custom village area can be seen from the division of space in a community house consisting of upper space (where the Gods and ancestral spirits), the living room (the place of man), the lower space (cattle), the porch of the house, and the kitchen. Biophysical characters in the area in the form of vegetation and animals. Vegetation found in the Praiyawang region consists of physical, economic and food functions. From the conclusions of this study, the proposed strategy is to develop the potential contained in the traditional village area as a cultural tourism area in accordance with its existence and not threaten the sustainability of the traditional village area. Kampung adat Praiyawang merupakan kampung tradisional di Desa Rindi, Kecamatan Rindi, Kabupaten Sumba Timur. Karakteristik lanskap kawasan kampung Praiyawang terdiri dari karakteristik fisik dan biofisik. Karakter fisik meliputi elemen pembentuk lanskap serta tata ruang kawasan. Elemen pembentuk lanskap kawasan Praiyawang yaitu, Uma batang (rumah menara), katuada (menhir), reti maramba (kuburan bangsawan), menhir, padang sabana. Tata ruang kawasan terdiri dari ruang makro, mesa dan mikro. Tata ruang makro meliputi tata ruang lanskap yang mendukung semua kehidupan masyarakat yang terdiri dari ruang hutan, pertanian, permukiman, serta padang sabana. Ruang meso merupakan bagian dari ruang makro yang terdiri dari lingkungan permukiman masyarakat kampung adat Praiyawang. Ruang meso terdiri dari elemen – elemen pembentuk permukiman yaitu Uma, Menhir, Reti, Penji, Katuanda dan Vegetasi. Penyebaran rumah masyarakat dikampung adat praiyawang memiliki pola permukiman yang melingkar dengan berjejeran mengelingi kuburan megalitikum. Ruang mikro meliputi rumah dan pekarangan. Tata ruang mikro kawasan kampung adat Praiyawang dapat dilihat dari pembagian ruang pada rumah masyarakat yang terdiri dari ruang atas(tempat para dewa dan arwah leluhur), ruang tengah (tempat manusia), ruang bawah (ternak) , teras rumah, dan dapur. Karakter biofisik pada kawasan berupa vegetasi dan satwa. Vegetasi yang terdapat pada kawasan Praiyawang terdiri dari fungsi fisik,ekonomi, dan pangan. Dari kesimpulan penelitian ini Strategi yang diusulkan adalah mengembangkan potensi yang terdapat pada kawasan kampung adat sebagai kawasan wisata budaya sesuai dengan keberadaan dan tidak mengancam keberlanjutan kawasan kampung adat tersebut.